Spatial analysis of hospital admissions for respiratory diseases during summer months in Berlin taking bioclimatic and socio-economic aspects into account - Scherber, Katharina; Langner, Marcel; Endlicher, Wilfried (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> International environmental health studies of the past years have discussed the impacts of heat stress on human health. In particular, respiratory morbidity has shown significant heat effects in European cities. Metropolitan areas such as Berlin are characterised by an intra-urban spatial variability in socio-economic and bioclimatic conditions that is assumed to result in spatial differences in respiratory health risks. In essence, the elderly, children and people with chronic diseases suffer from heat stress. A spatial epidemiological approach was chosen to map elevated risks for hospital admissions among > 64-year-olds with respiratory diseases (RD) during the summer months (June–September) from 2000 to 2009 and to link respiratory health risks to bioclimatic and socio-economic conditions in Berlin. The study aims to detect significant clusters with elevated relative risks for hospital admissions among > 64-year-olds with RD in due consideration of socio-economic conditions as a covariate for health outcomes. The findings from the purely spatial analysis show significant intra-urban disparities in the relative risks for hospital admissions among > 64-year-olds with RD. The highest relative risks within significant clusters were basically detected in the north-western and south-eastern city centre based on the study period 2000–2009 and also during the hot months of July and August in 2003 and 2006. The correlation analysis depicted significantly positive relationships between relative risks for hospital admissions among > 64-year-olds with RD and population density, socio-economic conditions and the annual mean number of days with heat loads on the basis of the period 1971–2000 and the average of the periods 1971–2000 and 2021–2050 at the zip code level in Berlin. To specifically implement health care intervention and prevention strategies into urban planning and to apply a directed practice of telemedicine for patients with chronic obstructive pulmonary diseases, spatial epidemiological analyses are an important approach to identifying heat-vulnerable urban areas. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>